Molecular elucidation of pancreatic elastase inhibition by baicalein - Ghosh, Debajeet; Bansode, Sneha; Joshi, Rakesh; Kolte, Baban; Gacche, Rajesh (Journal of Biomolecular Structure & Dynamics, 2022)
The serine protease, elastase exists in various forms and plays diverse roles in the human body. Pharmacological inhibition of elastase has been investigated for its therapeutic role in managing conditions such as diabetes, pneumonia and arthritis. Sivelestat, a synthetic molecule, is the only elastase inhibitor to have been approved by any major drug regulatory authority (PMDA, in this case) - but still has failed to attain widespread clinical usage owing to its high price, cumbersome administration and obscure long-term safety profile. In order to find a relatively better-suited alternative, screening was conducted using plant flavonoids, which yielded baicalein, a molecule that showed robust inhibition against Pancreatic Elastase inhibition (IC50: 3.53 mu M). Other than having a considerably lower IC(50)than sivelestat, baicalein is also cheaper, safer and easier to administer. While MicroScale Thermophoresis validated baicalein-elastase interaction, enzyme-kinetic studies, molecular docking and molecular dynamic simulation revealed the mode of inhibition to be non-competitive. Baicalein exhibited binding to a distinct allosteric site on the enzyme. The current study demonstrates the elastase inhibition properties of baicalein in an in-vitro and in-silico environment.
Keywords: Baicalein; elastase; Enzyme inhibition; molecular interaction; sivelestat

Comprehensive molecular and clinical investigation of approved Anti-HCV drugs repurposing against SARS-CoV-2 infection: a glaring gap between benchside and bedside medicine - Bansode, Sneha; Singh, Pawan Kumar; Tellis, Meenakshi; Chugh, Anita; Deshmukh, Narendra; Gupta, Mahesh; Verma, Savita; Giri, Ashok; Kulkarni, Mahesh; Joshi, Rakesh; Chaudhary, Dhruva (Vaccines, 2023)
The limited availability of effective treatment against SARS-CoV-2 infection is a major challenge in managing COVID-19. This scenario has augmented the need for repurposing anti-virals for COVID-19 mitigation. In this report, the anti-SARS-CoV-2 potential of anti-HCV drugs such as daclatasvir (DCV) or ledipasvir (LDP) in combination with sofosbuvir (SOF) was evaluated. The binding mode and higher affinity of these molecules with RNA-dependent-RNA-polymerase of SARS-CoV-2 were apparent by computational analysis. In vitro anti-SARS-CoV-2 activity depicted that SOF/DCV and SOF/LDP combination has IC50 of 1.8 and 2.0 mu M, respectively, comparable to remdesivir, an approved drug for COVID-19. Furthermore, the clinical trial was conducted in 183 mild COVID-19 patients for 14 days to check the efficacy and safety of SOF/DCV and SOF/LDP compared to standard of care (SOC) in a parallel-group, hybrid, individually randomized, controlled clinical study. The primary outcomes of the study suggested no significant difference in negativity after 3, 7 and 14 days in both treatments. None of the patients displayed any worsening in the disease severity, and no mortality was observed in the study. Although, the post hoc exploratory analysis indicated significant normalization of the pulse rate showed in SOF/DCV and SOF/LDP treatment vs. SOC. The current study highlights the limitations of bench side models in predicting the clinical efficacy of drugs that are planned for repurposing.
Keywords: antiviral; COVID-19; daclatasvir; ledipasvir; SARS-CoV-2; sofosbuvir